“Tears and perseverance”: An interpretative phenomenological analysis of mothers in raising children with dyslexia / Noor Amiera Alias - Alias, Noor Amiera (2016)
It is estimated that the number of children is 5 in every 100 pupils in primary school are potentially dyslexics in Malaysia. Dyslexia is a one types of Learning Disability which affects abilities in reading, spelling and writing. These issues increase motherhood experiences which subsequently give negative effects to mothers’ life such as physical health, psychological health and social relationship. However, those experiences are often found in literature from Western countries with other various conditions. To date, there is lack of literature regarding Malaysian mothers experience in raising children with dyslexia. The aims of this qualitative study are to illuminate the challenges, coping strategies and hopes of mothers' experiences in raising the children with dyslexia using a phenomenological approach. Data were collected from twenty mothers who have children with Dyslexia located at Dyslexia Association Malaysia (DAM) centre. Semi structured interview were conducted. The verbatim transcripts were analysed by using six steps Interpretative Phenomenological Analysis (IPA). Five super-ordinate themes emerged that describes the mothers’ experiences. The super-ordinate themes are, i.e., “Difficulty yet enduring” and "Selfperseverance” relating to challenges “Never mind, I will finds my ways” relating to coping strategies, “There is always improvement” and “/ wish ... ” relating to hopes emerged in this study. The present study has revealed experiences and knowledge that should be addressed by health professionals such as occupational therapy to construct an effective intervention to mothers raising a child with Dyslexia. The findings provide a deeper understanding to the occupational therapy to support mothers or families effectively.